Robust Tuning of PI-PD Controller for Antilock Braking System - Ali, Hazem I.; Saeed, Ali Hadi (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper presents the design of robust four parameters (two degree of freedom) PI-PD controller based on Kharitonov theorem for antilock braking system. The Particle Swarm Optimization (PSO) method is used to tune the parameters of the proposed controller based on Kharitonov theorem to achieve the robustness over a wide range of system parameters change. The proposed cost function combines the time response specifications represented by the model reference and the frequency response specifications represented by gain margin and phase margin and the control signal specifications. The model reference control is used because of the antilock braking system is originally nonlinear and has different operating points. The robust stability is guaranteed by applying the Kharitonov theorem. Three types of road conditions (dry asphalt, gravel and icy) are used to test the proposed controller.